Whole-Genome Sequence of Endophytic Bacteria Associated with Poison Ivy Vine (Toxicodendron radicans) - Gan, Han Ming *; Penix, Trevor S; Wengert, Peter C; Wong, Narayan H; Hudson, Andre O; Kumar, Girish; Savka, Michael A (American Society for Microbiology, 2023)
Here, we report the genome assemblies of 11 endophytic bacteria, isolated from poison ivy vine (Toxicodendron radicans). Five species belonging to the genus Pseudomonas, two species of Curtobacterium, one strain of Pantoea agglomerans, and one species from the Bacillus, Cellulomonas, and Enterobacter genera were isolated from the interior tissue of poison ivy.